New traveling wave solutions by the extended generalized Riccati equation mapping method of the (2 + 1) -dimensional evolution equation - Naher, Hasibun; Abdullah, Farah Aini (© 2012 Journal of Applied Mathematics, 2016)
This article was published in the Journal of Applied Mathematics [© 2012 Hasibun Naher and Farah Aini Abdullah.] and the definite version is available at : http://dx.doi.org/10.1155/2012/486458 The Journal's website is at:https://www.hindawi.com/journals/jam/2012/486458/